2004
DOI: 10.1191/0265532204lt284oa
|View full text |Cite
|
Sign up to set email alerts
|

Teacher assessment: the concept of ‘diagnostic competence’

Abstract: In the light of recent trends in educational assessment, language testing and the pedagogical discussion about new teacher roles, this article focuses on the skills and abilities required of a language teacher wishing to respond to these developments, with specific reference to the primary (elementary) foreign language classroom. A new concept is introduced ‘diagnostic competence’ defined as the ability to interpret foreign language growth in individual children. In order to arrive at this conceptualization, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 13 publications
2
32
0
1
Order By: Relevance
“…The results regarding the teacher's assessment practices were in line with the findings of the first phase of the large-scale project and other international studies carried out in this field (Butler, 2009a;Edelenbos & Kubanek-German, 2004;Rea-Dickins & Gardner, 2000). W hile describing the students' language knowledge, the unclear terms Anikó used revealed that she had difficulties with capturing her students' level of ability.…”
Section: Classroom Assessmentsupporting
confidence: 82%
See 2 more Smart Citations
“…The results regarding the teacher's assessment practices were in line with the findings of the first phase of the large-scale project and other international studies carried out in this field (Butler, 2009a;Edelenbos & Kubanek-German, 2004;Rea-Dickins & Gardner, 2000). W hile describing the students' language knowledge, the unclear terms Anikó used revealed that she had difficulties with capturing her students' level of ability.…”
Section: Classroom Assessmentsupporting
confidence: 82%
“…In a study carried out in Germany and the Netherlands, Edelenbos and Kubanek-German (2004) observed the diagnostic behavior of primary school teachers of English. The results revealed that many teachers found the task of capturing their students' level of ability challenging.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the reliability of teacher's assessment has been discussed in the literature and there is evidence that teacher's assessments vary greatly [11] [17]. In addition, general assessment studies on teacher behavior in language classes have shown that teachers spend a relatively little time assessing individual student's performance [7]. It is apparent that if the assessment of the student's learning depends on the teacher's individual assessment, there may be problems with how objective the evaluation would be.…”
Section: Literature Reviewmentioning
confidence: 99%
“…V nejužším pojetí se může jednat jen o hodnocení výkonu žáka (např. Arnold, 1999) nebo o schopnost zacházet s testovými materiály (Edelenbos & Kubanek-German, 2004). V širším pojetí diagnostické kompetence (a u konceptů příbuzných) je předmětem diagnostikování celá třída (Švec, 1999) nebo komplexní výuková situace (Janík et al, 2009;Seidel, Blomberg, & Stürmer, 2010).…”
Section: Diagnostická Kompetenceunclassified